2021
DOI: 10.1177/1055665620987684
|View full text |Cite
|
Sign up to set email alerts
|

Furlow Palatoplasty: Should We Also Focus on the Size of the Nasopharynx?

Abstract: Objectives: (1) To determine the incidence rate of velopharyngeal dysfunction (VPD) according to 7 speech criteria post-Furlow palatoplasty. (2) To find an anatomical measurement of the cleft palate (or combination of measurements) associated with the occurrence of VPD. Study design: Retrospective cohort study. Participants and Methods: Fifty-six patients with cleft palate ± cleft lip underwent palatoplasty with the Furlow technique at the age of 10 months. Pre-and post-palatoplasty cleft palate measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…20 Its effect on the FP outcome in correction of overt cleft palate or secondary VPI has been proven by numerous studies but is inconclusive among the SMCP population. 6,20,29,60,65,66 In this study, preoperative VCR was not indicated as predictive of FP outcome.…”
Section: Discussioncontrasting
confidence: 58%
“…20 Its effect on the FP outcome in correction of overt cleft palate or secondary VPI has been proven by numerous studies but is inconclusive among the SMCP population. 6,20,29,60,65,66 In this study, preoperative VCR was not indicated as predictive of FP outcome.…”
Section: Discussioncontrasting
confidence: 58%
“…Nevertheless, we can fi nd many comparison studies dealing with late complications such as velopharyngeal insuffi ciency (VFI), orofacial fi stula or decreased growth of maxilla (18,19). In the past 5 years , there has been an increased number of articles dealing with other factors affecting long-term surgical results such as size of the nasopharynx and age of children undergoing palatoplasty (20,21). The reviews are comparing usually two different procedures from the most frequent palatoplasty approaches (according to von Langenbeck, Veau-Wardill-Kilner and double opposite reverse Z-palatoplasty according to Furlow).…”
Section: Introductionmentioning
confidence: 99%